Catalyst composition and catalyst layer for fuel cell using catalyst composition
Incorporating a hydrophilic polymer into the catalyst composition for polymer electrolyte fuel cells improves proton and electron conductivity, enhancing power generation characteristics by improving water transport and mechanical strength in the catalyst layer.
Patent Information
- Application Number
- JP2021200865
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-10
- Publication Date
- 2025-01-23
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing catalyst layers in polymer electrolyte fuel cells do not effectively utilize water-soluble polymers to enhance power generation characteristics, as they are primarily used in electrolyte membranes and composite catalyst production, not in the catalyst layers.
Incorporating a hydrophilic polymer, such as polyvinyl alcohol or polyvinylpyrrolidone, into the catalyst composition for the catalyst layer, along with a metal catalyst, polymer electrolyte, and catalyst support, to improve proton conductivity, electron conductivity, and water transport.
The catalyst composition enhances power generation characteristics by improving proton conductivity, electron conductivity, and water transport, leading to better performance and mechanical strength in the catalyst layer.
Smart Images

Figure 2025010637000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst composition and a catalyst layer for a fuel cell using the catalyst composition. [Background technology]
[0002] A polymer electrolyte fuel cell (hereinafter, also referred to as a fuel cell) converts energy generated by a chemical reaction into electrical energy. The fuel cell has a membrane electrode assembly, which has an anode catalyst layer, a cathode catalyst layer, and a polymer electrolyte membrane sandwiched between the catalyst layers, and each catalyst layer has a gas diffusion layer on the outside. The catalyst layer includes a catalyst supported on a catalyst carrier and an electrolyte. The cathode catalyst layer requires the supply of three things to cause a chemical reaction: protons from the electrolyte membrane, electrons from the current collector, and oxygen. The cathode catalyst layer is therefore required to have the ability to transmit oxygen and to transport water.
[0003] Non-Patent Document 1 reviews the effects of membrane crosslinking when a water-soluble polymer is blended with a polymer or formed into a membrane. Patent Document 1 reports on a composite catalyst for fuel cells using a water-soluble polymer, a method for producing a composite catalyst for fuel cells, and a method for producing an electrode catalyst layer for fuel cells. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Polymers 2012, Vol. 4, pp. 913-963 [Patent documents]
[0005] [Patent Document 1] JP 2009-212008 A Summary of the Invention [Problem to be solved by the invention]
[0006] There are cases where a water-soluble polymer is formed into a membrane and used in an electrolyte membrane for the purpose of improving power generation characteristics, as reported in Non-Patent Document 1. In addition, there are cases where a water-soluble polymer is used in a process for producing a composite catalyst for a fuel cell, as reported in Patent Document 1, but there are no cases where a water-soluble polymer material is added to an ink for applying a catalyst for a solid polymer electrolyte fuel cell and used in the catalyst layer of the solid polymer electrolyte fuel cell. The present invention has been made in light of the above-mentioned circumstances, and has an object to provide a catalyst composition for constituting a catalyst layer of a polymer electrolyte fuel cell, which can improve the power generation characteristics of the polymer electrolyte fuel cell. [Means for solving the problem]
[0007] As a result of extensive investigations, the inventors have found that by adding a hydrophilic polymer to a catalyst composition that constitutes a catalyst for a polymer electrolyte fuel cell, the catalyst layer of the polymer electrolyte fuel cell exhibits excellent power generation characteristics.
[0008] The present invention based on these findings includes, for example, the following [1] to [8]. [1] A catalyst composition comprising a hydrophilic polymer (a) and a metal catalyst (b). [2] The catalyst composition according to [1], further comprising a polymer electrolyte (c). [3] The catalyst composition according to [1] or [2], wherein the hydrophilic polymer (a) is at least one selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, poly(4-vinylpyridine) and poly(2-vinylpyridine). [4] The catalyst composition according to any one of [1] to [3], which is for use in a catalyst layer of a polymer electrolyte fuel cell. [5] A catalyst layer for a polymer electrolyte fuel cell, comprising the catalyst composition according to any one of [1] to [4]. [6] A membrane electrode assembly having a polymer electrolyte membrane, a gas diffusion layer, and the catalyst layer for a solid polymer electrolyte fuel cell according to [5]. [7][6] A polymer electrolyte fuel cell having a membrane electrode assembly. [8] A method for improving the power generation characteristics of a polymer electrolyte fuel cell by using a hydrophilic polymer in the catalyst layer of the polymer electrolyte fuel cell. Effect of the Invention
[0009] The catalyst composition of the present invention can be used in an embodiment to form a catalyst layer of a polymer electrolyte fuel cell, and can improve the power generation characteristics of the polymer electrolyte fuel cell. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing a schematic configuration of a polymer electrolyte fuel cell; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention relates to a catalyst composition comprising a mixture of a hydrophilic polymer (a) and a metal catalyst (b).
[0012] ≪Catalyst composition≫ A catalyst composition is described herein.
[0013] <Hydrophilic polymer (a)> The catalyst composition includes a hydrophilic polymer (a). The hydrophilic polymer (a) exhibits hydrophilicity by containing polar or charged functional groups in the polymer, and has many functional groups in the polymer that have a strong interaction with water. Examples of functional groups that have a strong interaction with water include ionic groups, hydroxy groups, amino groups, amide groups, and ether groups. The weight average molecular weight measured by gel permeation chromatography is 10,000 to 3,000,000, preferably 20,000 to 2,000,000, and more preferably 30,000 to 1,500,000.
[0014] Examples of the hydrophilic polymer (a) include polyvinyl alcohol, polyacrylamide, polyethyleneimine, polyacrylic acid, polyvinylpyrrolidone, polypyridine, poly(4-vinylpyridine), poly(2-vinylpyridine), poly(4-vinylpyridine-co-styrene), etc., which may be used alone or in combination of two or more. Among these, polyvinyl alcohol, polyvinylpyrrolidone, poly(4-vinylpyridine), and poly(2-vinylpyridine) are preferred, and polyvinyl alcohol or polyvinylpyrrolidone is more preferred.
[0015] <Metal catalyst (b)> The catalyst composition includes a metal catalyst. Examples of metal catalysts include metals such as platinum, gold, silver, ruthenium, iridium, rhodium, palladium, osmium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, and aluminum, as well as alloys thereof and core-shell types of these metals. The main function of the catalyst component is to cause an electrochemical reaction.
[0016] <Polymer electrolyte (c)> The catalyst composition preferably comprises a polymer electrolyte (c). Examples of the polymer electrolyte include fluorine-based sulfonic acid polymers, hydrocarbon-based sulfonic acid polymers, and partially fluorinated hydrocarbon-based sulfonic acid polymers, such as Nafion (registered trademark, manufactured by DuPont), Aquivion (registered trademark, manufactured by Solvay), Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.), and Aciplex (registered trademark, manufactured by Asahi Kasei Co., Ltd.). The polymer electrolyte is preferably a perfluoro acid polymer, such as Nafion (registered trademark, manufactured by DuPont), Aquivion (registered trademark, manufactured by Solvay), Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.), and Aciplex (registered trademark, manufactured by Asahi Kasei Co., Ltd.). The main function of the polymer electrolyte in the catalyst layer is to conduct protons.
[0017] <Catalyst support (d)> The catalyst composition preferably comprises a catalyst support (d). Examples of catalyst supports include carbon blacks such as channel black, furnace black, thermal black, and Ketjen black; activated carbons obtained by carbonizing and activating various materials containing carbon atoms; coke, natural graphite, artificial graphite, and graphitized carbon. Of the above, carbon black is preferred as a catalyst support because of its high specific surface area and excellent electronic conductivity. The main function of a catalyst support is to conduct electrons. Another main function of a catalyst support is the transport of fuel gas and water through the pores of the catalyst support.
[0018] <Binding agent (e)> The catalyst composition preferably contains a binder (e). Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), ethylene-propylene-diene copolymer (EPDM), fluorine-based sulfonic acid polymers such as Nafion (registered trademark, manufactured by DuPont Co., Ltd.), Aquivion (registered trademark, manufactured by Solvay K.K.), Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.), and Aciplex (registered trademark, manufactured by Asahi Kasei Co., Ltd.). The binder binds the catalyst carriers together in the catalyst layer and suppresses a decrease in electronic conductivity in the electrode catalyst.
[0019] <Solvent (f)> The catalyst composition preferably comprises a solvent (f). Examples of the solvent include water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, pentanol, dimethyl sulfoxide, N,N-dimethylformamide, chloroform, dichloromethane, diethyl ether, 1,4-dioxane, and tetrahydrofuran. The solvent is preferably water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, 1,4-dioxane, or tetrahydrofuran. Two or more of the above-mentioned solvents may be mixed and used. From the viewpoint of suppressing re-aggregation of the catalyst composition, making it easy to apply, and further suppressing the solvent from remaining in the catalyst layer, the solvent used for the catalyst composition is more preferably water, ethanol, 1-propanol, 2-propanol, or tetrahydrofuran.
[0020] <Composition> The content of each component in the catalyst composition is appropriately adjusted according to the power generation characteristics and is not particularly limited, but from the viewpoint of power generation characteristics, the hydrophilic polymer (a) is preferably 0.01 to 30 mass% and the metal catalyst (b) is preferably 10 to 40 mass% in 100 mass% of the solid content of the catalyst composition. When other optional components are included, the polymer electrolyte (c) is preferably 15 to 45 mass%, the catalyst carrier (d) is preferably 15 to 45 mass%, and the binder (e) is preferably 0 to 5 mass% in 100 mass% of the catalyst composition. It is preferable from the viewpoint of power generation characteristics that the content of each component is within the above range. When an electrode catalyst is used, the weight of the metal catalyst and the weight of the catalyst carrier are calculated separately. The amount of the solvent (f) used is not particularly limited as long as it can adjust the slurry state of the composition and maintain a coatable slurry state.
[0021] <Method of producing catalyst composition> The catalyst composition is obtained by mixing a hydrophilic polymer (a), a metal catalyst (b), and an optional polymer electrolyte (c), a catalyst support (d), a binder (e), and a solvent (f). As a mixing method, in addition to stirring using a normal stirring device, stirring using ultrasonic waves, etc. can be mentioned.
[0022] ≪Polymer fuel cell≫ FIG. 1 is a cross-sectional view showing a schematic configuration of a solid polymer electrolyte fuel cell. A solid polymer electrolyte fuel cell 100 has an anode catalyst layer 103, a cathode catalyst layer 105, and a polymer electrolyte membrane 107 sandwiched between the two catalyst layers, and each catalyst layer has a gas diffusion layer (hereinafter abbreviated as "GDL") 101 on the outside. This configuration is called a membrane electrode assembly (hereinafter abbreviated as "MEA"). In a solid polymer electrolyte fuel cell, this MEA is usually sandwiched between separators 109.
[0023] The method for producing the anode catalyst layer 103 and the cathode catalyst layer 105 will be described. After preparing the catalyst composition of the present invention as a catalyst ink, the catalyst ink is applied to a target substrate and dried to produce a catalyst layer. Thus, the catalyst layer contains the catalyst composition of the present invention. By using the catalyst composition of the present invention as a catalyst ink, it is possible to improve functions and performance, such as suppressing the decrease in electronic conductivity, improving proton conductivity, improving fuel gas diffusivity, making water transport more efficient, and improving the mechanical strength of the catalyst layer.
[0024] The target substrate may be, for example, a polymer electrolyte membrane, a GDL, or a sheet made of a fluororesin, and the catalyst layer may be produced by a known production method. When the catalyst ink is applied to a sheet made of a fluororesin, the applied catalyst layer is transferred to the polymer electrolyte membrane. A sheet made of polytetrafluoroethylene (PTFE) is generally used as the sheet made of a fluororesin.
[0025] At least one of the anode catalyst layer 103 and the cathode catalyst layer 105 is produced from the catalyst composition of the present invention and contains a hydrophilic polymer (a). From the viewpoint of suppressing an increase in overvoltage during high current driving, it is preferable to use the catalyst composition of the present invention in at least the cathode catalyst layer 105. As described above, the hydrophilic polymer (a) is used as an additive in the catalyst ink that forms the catalyst layer, which differs from a membrane formed from the hydrophilic polymer (a).
[0026] The hydrophilic polymer (a) has voids inside the material, and the effect of these voids is to improve gas permeability and water transport. Therefore, it is believed that when used in the catalyst layer of a polymer electrolyte fuel cell, it can improve power generation characteristics.
[0027] The anode catalyst layer 103 and the cathode catalyst layer 105 each contain a catalyst component and a polymer electrolyte in addition to the hydrophilic polymer (a), and preferably further contain a catalyst support and a binder for supporting the catalyst component. A catalyst supported on a catalyst support is called an electrode catalyst. In this specification, the anode catalyst layer 103 and the cathode catalyst layer 105 may be abbreviated to catalyst layers. In this specification, the electrode catalyst is defined as being composed of a metal catalyst and a catalyst support.
[0028] An example of the composition of the catalyst ink is a composition containing the above-mentioned solvent, platinum as a catalyst, carbon black as a catalyst support, Nafion (registered trademark, manufactured by DuPont Co., Ltd.) as a polymer electrolyte, and a hydrophilic polymer (a). Furthermore, the catalyst ink is produced by preferably subjecting the catalyst composition of the present invention to a crushing treatment, and a catalyst ink for a polymer electrolyte fuel cell is obtained.
[0029] Examples of the disintegration treatment include a dry disintegration treatment and a wet disintegration treatment. Examples of the dry disintegration treatment include a ball mill, a planetary mill, a pin mill, a jet mill, and the like. Examples of the wet disintegration treatment include an ultrasonic homogenizer, an ultrasonic disperser, a bead mill, a sand grinder, a homogenizer, a wet jet mill, and the like. Among these, preferred disintegration treatments are a ball mill, an ultrasonic homogenizer, an ultrasonic disperser, and a homogenizer, and the ultrasonic homogenizer and the ultrasonic disperser are particularly preferred. The solvent used in the wet disintegration treatment is not particularly limited, but the solvent used in the catalyst ink can be used.
[0030] The hydrophilic polymer (a) is used when preparing the catalyst ink. The catalyst ink is then applied to form a catalyst layer on a polymer electrolyte membrane to produce a membrane electrode assembly (MEA). By incorporating the MEA into a single cell, improved power generation characteristics can be achieved.
[0031] The proportion of the hydrophilic polymer (a) used in the catalyst layer is calculated by the following formula: In the following calculation formula, the masses of the electrode catalyst, hydrophilic polymer (a), polymer electrolyte, and binder are calculated based on the solid masses minus the water and solvent.
[0032] Percentage of hydrophilic polymer (a) used (mass%) = [hydrophilic polymer (a) (mass) / [total mass in catalyst layer (solid mass)]] × 100 (mass%) = [hydrophilic polymer (a) (mass) / [electrode catalyst (mass) + optional polymer electrolyte (mass) + optional binder (mass) + optional catalyst support (mass) + hydrophilic polymer (a) (mass)]] × 100 (mass%) The proportion of the hydrophilic polymer (a) used in the catalyst layer, as determined from the above formula, is preferably from 0.01 to 30 mass %, more preferably from 0.1 to 20 mass %, from the viewpoint of efficiently supplying oxygen gas and discharging water.
[0033] Examples of materials for the polymer electrolyte membrane 107 include fluorine-based sulfonic acid polymers such as Nafion (registered trademark, manufactured by DuPont), Aquivion (registered trademark, manufactured by Solvay), Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.), and Aciplex (registered trademark, manufactured by Asahi Kasei Corporation), hydrocarbon-based sulfonic acid polymers, and partially fluorinated hydrocarbon-based sulfonic acid polymers.
[0034] The gas diffusion layer 101 is not particularly limited, but a conductive porous material is preferably used, and examples of such materials include carbonaceous paper and nonwoven fabric, felt, nonwoven fabric, etc. Furthermore, some GDLs are coated with a layer called a microporous layer (hereinafter abbreviated as "MPL"), which is a coating layer mainly composed of a water-repellent resin and a carbon material, and it has been reported that this layer effectively transports water during power generation in a polymer electrolyte fuel cell, and the catalyst layer containing the hydrophilic polymer (a) can also use a gas diffusion layer having this MPL. In the power generation test of the present invention, water-repellent carbon paper, which is a GDL having this MPL, was used. EXAMPLES
[0035] Synthesis examples and examples of the present invention will be described in more detail below, but the present invention is not limited thereto. The analytical apparatus and conditions used in the examples are as follows. The weight average molecular weights described in the examples are catalog values.
[0036] <Power generation test of polymer electrolyte fuel cell A> The fabricated MEA is 2After incorporating it into a single cell (JARI standard cell, manufactured by FC Development Co., Ltd.) with an electrode area of 100 μm, a power generation test of the polymer electrolyte fuel cell was conducted. Evaluation was performed using a polymer electrolyte fuel cell evaluation system (AutoPEM, manufactured by Toyo Corporation) at a temperature of 80°C, a relative humidity of 95%, and a hydrogen gas flow of 0.10 L / min and an air gas flow of 0.33 L / min, and the current density, voltage, and open circuit voltage (hereinafter abbreviated as "OCV") were measured. Note that OCV is the potential when no voltage or current is applied to the single cell.
[0037] <Example 1> An electrode catalyst (Tanaka Kikinzoku Kogyo Co., Ltd., platinum content: 46.5 mass%, carbon carrier amount: 53.5 mass%, product name "TEC10E50E"), a hydrophilic polymer polyvinylpyrrolidone (Tokyo Chemical Industry Co., Ltd., K 30, weight average molecular weight 40,000), a Nafion dispersion solution (Wako Pure Chemical Industries, Ltd., product name "5% Nafion Dispersion Solution DE520 CS type"), and 2-propanol (Wako Pure Chemical Industries, Ltd.) were added in this order to a glass vial, and then ultrasonic waves were applied for 5 minutes using an ultrasonic cleaner ASU-6 manufactured by AS ONE Corporation with the oscillation power set to "High" to prepare catalyst composition A.
[0038] Preparation conditions for catalyst composition A: Nafion ratio (mass%) =[Nafion solid content (mass) / [electrode catalyst (mass) + Nafion solid content (mass)]]×100 (mass%) was set to 26 mass %. Specifically, when the mass of the electrode catalyst was 27.5 mg, the composition was prepared by setting the hydrophilic polymer polyvinylpyrrolidone (2.0 mg), the Nafion dispersion solution (194.0 mg), and 2-propanol (1 mL). The Nafion dispersion solution (194.0 mg) corresponds to the solid content of Nafion (9.7 mg).
[0039] Hydrophilic polymer ratio (mass%) =[Hydrophilic polymer (mass) / [electrode catalyst (mass) + Nafion solid content (mass) + hydrophilic polymer (mass)]]×100 (mass%) was adjusted to 5% by mass.
[0040] Application conditions for catalyst composition A: The catalyst composition A was applied to a 130μm-thick Teflon sheet with a target of 6.5cm x 6.5cm and an applicator (the target and applicator were manufactured by Nissan Chemical Industries, Ltd.) using the entire amount of the prepared catalyst composition A. 2 A decal was created on a Teflon sheet with a catalyst layer containing 0.3 mg of platinum per unit area, and then cut out into a decal measuring 1 cm x 1 cm.
[0041] Steps for preparing MEA: The membrane electrode assembly (MEA) was fabricated using a polymer electrolyte membrane, a gas diffusion layer (GDL), and decals using catalyst ink on both the anode and cathode sides. The GDL was carbon paper with MPL (manufactured by SGL Carbon Japan Co., Ltd., product name "28BC").
[0042] A Nafion 212 membrane (registered trademark, manufactured by DuPont Co., Ltd., purchased from Chemix Co., Ltd., film thickness: 50 μm) cut into a 5 cm x 5 cm square was placed in the center as a polymer electrolyte membrane, and a decal (area 1 cm x 1 cm) with a catalyst layer on a Teflon sheet was placed on both sides of it, and then thermocompression bonding was performed under the conditions of upper and lower plate temperatures of 132°C, load of 0.6 kN, and compression time of 40 seconds, and the Teflon sheet was peeled off to produce a catalyst coated membrane (hereinafter abbreviated as "CCM"). The platinum weight of the anode and cathode was confirmed by the mass difference between the decal and after transfer.
[0043] The GDL was made of carbon paper (manufactured by SGL Carbon Japan, product name "28BC", area 1 cm x 1 cm) and was stacked on both the anode and cathode sides with the MPL layer side facing the polymer electrolyte membrane. The JARI standard cell was then tightened with a torque wrench in 1 Nm increments up to 4 Nm to press the GDL and CCM together. Using the fabricated MEA, a power generation test A of the polymer electrolyte fuel cell was carried out. The OCV was 0.93 V. The voltage and current density results are shown in Table 1.
[0044] <Example 2> The same experimental procedure as in Example 1 was carried out, except that a hydrophilic polymer, polyvinyl alcohol (manufactured by Tokyo Chemical Industry Co., Ltd., polymerization degree 1700, weight average molecular weight 75,000), was used. The OCV was 0.93 V. The results of the voltage and current density are shown in Table 1.
[0045] <Comparative Example 1> An MEA was produced in the same manner as in Example 1, except that the catalyst composition was prepared without using polyvinylpyrrolidone, which is a hydrophilic polymer.
[0046] Using the fabricated MEA, a power generation test A of the polymer electrolyte fuel cell was carried out. The OCV was 0.94 V. The results of the voltage and current density are shown in Table 1.
[0047] [Table 1]
[0048] In comparison with Comparative Example 1, in which a power generation test of a polymer electrolyte fuel cell was conducted under the same conditions except for whether or not a hydrophilic polymer was used in the catalyst layer of the polymer electrolyte fuel cell, the current range was 1.0 A / cm 2 In the high current region above, Example 1 gave better results, with the current region being 1.2 A / cm 2 In the above-mentioned high current region, better results were obtained in Example 2, and it is considered that the addition of the hydrophilic polymer had the effect of improving the power generation characteristics. [Industrial Applicability]
[0049] The catalyst composition of the present invention is expected to improve power generation characteristics when used in the catalyst layer of a polymer electrolyte fuel cell. [Explanation of symbols]
[0050] 100 Polymer electrolyte fuel cell 101 Gas diffusion layer 103 Anode catalyst layer 105 Cathode catalyst layer 107 Polymer electrolyte membrane 109 Separator
Claims
1. A catalyst composition comprising a mixture of a hydrophilic polymer (a) and a metal catalyst (b).
2. The catalyst composition according to claim 1, further comprising a polymer electrolyte (c).
3. 3. The catalyst composition according to claim 1, wherein the hydrophilic polymer (a) is at least one selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, poly(4-vinylpyridine) and poly(2-vinylpyridine).
4. The catalyst composition according to any one of claims 1 to 3, which is used for a catalyst layer of a polymer electrolyte fuel cell.
5. A catalyst layer for a polymer electrolyte fuel cell comprising the catalyst composition according to any one of claims 1 to 4.
6. A membrane / electrode assembly comprising a polymer electrolyte membrane, a gas diffusion layer, and the catalyst layer for a polymer electrolyte fuel cell according to claim 5.
7. A polymer electrolyte fuel cell comprising the membrane electrode assembly according to claim 6.
8. A method for improving the power generation characteristics of a polymer electrolyte fuel cell by using a hydrophilic polymer in a catalyst layer of the polymer electrolyte fuel cell.
Citation Information
Patent Citations
Composite catalyst of fuel cell, method of manufacturing composite catalyst of fuel cell, method of manufacturing electrocatalyst layer of fuel cell, and fuel cell
JP2009212008A